Adsorbent-Embedded Polymeric Membranes for Efficient Dye-Water Treatment - Junaid Saleem (14670322) (2024)
Traditional bulk adsorbents, employed for the removal of dyes and metal ions, often face the drawback of requiring an additional filtration system to separate the filtrate from the adsorbent. In this study, we address this limitation by embedding the adsorbent into the polymer matrix through a process involving dissolution–dispersion, spin-casting, and heat-stretching. Selective dissolution and dispersion facilitate the integration of the adsorbent into the polymer matrix. Meanwhile, spin-casting ensures the formation of a uniform and thin film structure, whereas heat-induced stretching produces a porous matrix with a reduced water contact angle. The adsorbent selectively captures dye molecules, while the porous structure contributes to water permeability. We utilized inexpensive and readily available materials, such as waste polyethylene and calcium carbonate, to fabricate membranes for the removal of methylene blue dye. The effects of various parameters, such as polymer-adsorbent ratio, initial dye concentration, and annealing temperature, were investigated. Equilibrium data were fitted to Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich isotherms. The equilibrium data were best represented by the Langmuir isotherm, with maximum adsorption capacity of 35 mg/g and 43 mg/g at 25 °C and 45 °C, respectively. The membranes can be regenerated and recycled with a 97% dye removal efficiency. The study aims to present a template for adsorbent-embedded polymeric membranes for dye removal, in which adsorbent can be tailored to enhance adsorption capacity and efficiency. Other Information Published in: Polymers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/polym16111459